2018
DOI: 10.1177/1049732318761366
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Meso-Macro Practice Tensions in Using Patient-Reported Outcome and Experience Measures in Hospital Palliative Care

Abstract: This article applies a micro-meso-macro analytical framework to understand clinicians' experiences and perspectives of using patient-reported outcome and experience measures (PROMs and PREMs) in routine hospital-based palliative care. We structure our discussion through qualitative analysis of a design and implementation project for using an electronic tablet-based tool among hospital-based palliative clinicians to assess patients' and their family caregivers' quality of life concerns and experiences of care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…The contextual factors were grouped into how they fit within the patient work system (either in the macroergonomic triad of physical, social, and organizational factors or within the microergonomic triad of person-task-tools) [ 2 , 14 , 32 ]. As the patient work system has 3 layers, with households and communities comprising the mesoergonomic layer between the macro and microergonomic contexts, we also grouped contextual factors based on the level (macro, meso, or micro) at which they affected patient work tasks [ 33 , 34 ]. Although Holden et al [ 100 ] have identified mesoergonomics as the study of the relationship between variables in different layers of an ergonomics system, the meso contextual factors we identified here correspond to factors that sit between the micro- and macroergonomics levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contextual factors were grouped into how they fit within the patient work system (either in the macroergonomic triad of physical, social, and organizational factors or within the microergonomic triad of person-task-tools) [ 2 , 14 , 32 ]. As the patient work system has 3 layers, with households and communities comprising the mesoergonomic layer between the macro and microergonomic contexts, we also grouped contextual factors based on the level (macro, meso, or micro) at which they affected patient work tasks [ 33 , 34 ]. Although Holden et al [ 100 ] have identified mesoergonomics as the study of the relationship between variables in different layers of an ergonomics system, the meso contextual factors we identified here correspond to factors that sit between the micro- and macroergonomics levels.…”
Section: Resultsmentioning
confidence: 99%
“…Work tasks were identified from the included articles, were clustered based on common themes that emerged, and were consulted against Dack et al’s model [ 31 ]. Contextual factors were grouped according to where they fit within the dimensions outlined in the patient work framework (patient, tasks, tools, physical, social, and organizational) [ 2 , 14 , 32 ] and the level at which they exert influence (micro, meso, or macro) [ 33 , 34 ]. We identified microlevel contextual factors as aspects that only affected the patient’s body or were psychological factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect indicators of need assume that patients consider there is legitimacy in discussing their support needs with health care professionals, that they understand the holistic nature of supportive care and have the opportunity and confidence to contribute to discussions on what they require to manage life with their illness. Evidence suggests this is not always the case 42,43 and therefore there is a need for designed-for-purpose tools, such as the SNAP tool. The SNAP tool has therefore been specifically developed to facilitate delivery of a holistic, person-centred approach for the identification of patient support needs: the Support Needs Approach for Patients (SNAP).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors identified include the use of technology, having the appropriate infrastructure in place, embedding PROMs into routine workflow, improving the interpretability of PROMs data, and engaging clinicians in the planning phase of the intervention [35]. Finally, a key element identified by clinicians is the linkage of PROMs with tools to support the clinical management of symptoms or problems identified by assessments [37]. For example, if a patient identifies problems with anxiety or depression, clinicians should have readily available treatment protocols to follow to alleviate those symptoms [35,36].…”
Section: Proms In Clinical Practicementioning
confidence: 99%